From challenges to opportunities - Søgaard, Helene Albinus (2015)
The increasingly dense and paved cities often situated in coastal areas, are challenged by climate change that intensifies damages to urban infrastructure. Through a theoretical framework combining Advocacy Coalition Framework with organizational learning theory of ‘Ba’, the public knowledge creation processes on climate adaptation in Danish municipalities are analyzed in an empirical study. Extreme weather events are found to have initiated a series of political responses, and the knowledge creation processes are deemed essential in finding innovative and flexible solutions to the uncertainties inherent in future climate changes. However, the current national regulation of the water sector are dominated by three major political priorities (analyzed as belief systems) that simultaneously promote and prohibit an adequate facilitation of the different learning contexts of ba essential for knowledge creation in the municipalities. The thesis concludes that a more systematic and proactive gathering, synthesizing and analyzing of practical experience gained at the municipal level during the implementation of climate adaptation projects bears vital insights for the development of a more coherent national regulative framework on climate adaptation, in which innovative learning processes could be improved.